2018
DOI: 10.1111/ejn.13970
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral amygdala, nicotinic cholinergic receptors, and nicotine: Pharmacological effects and addiction in animal models and humans

Abstract: The amygdala is involved in processing incoming information about rewarding stimuli and emotions that denote danger such as anxiety and fear. Bi-directional neural connections between basolateral amygdala (BLA) and brain regions such as nucleus accumbens, prefrontal cortex, hippocampus, and hindbrain regions regulate motivation, cognition, and responses to stress. Altered local regulation of BLA excitability is pivotal to the behavioral disturbances characteristic of posttraumatic stress disorder, and relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…Our results also show increased activity in BLA during context-induced relapse after punishment-imposed abstinence. The role of BLA in cue- and stress-induced reinstatement of nicotine-seeking has been demonstrated previously ( Khaled et al, 2014 ; Sharp, 2019 ; Xue et al, 2017 ; Yu and Sharp, 2015 ), but to our knowledge this is the first time that BLA has been implicated in context-induced relapse of nicotine-seeking. We also show increased activation in the aBLA → aIC pathway during context-induced relapse.…”
Section: Discussionsupporting
confidence: 55%
“…Our results also show increased activity in BLA during context-induced relapse after punishment-imposed abstinence. The role of BLA in cue- and stress-induced reinstatement of nicotine-seeking has been demonstrated previously ( Khaled et al, 2014 ; Sharp, 2019 ; Xue et al, 2017 ; Yu and Sharp, 2015 ), but to our knowledge this is the first time that BLA has been implicated in context-induced relapse of nicotine-seeking. We also show increased activation in the aBLA → aIC pathway during context-induced relapse.…”
Section: Discussionsupporting
confidence: 55%
“…Dysfunction of the amygdala has been implicated in a number of different neurodevelopmental disorders and psychopathologies ( Davis and Whalen, 2001 ; Belkhiria et al, 2020 ; Cui et al, 2020 ), such as depression ( Abercrombie et al, 1998 ), social anxiety disorder ( Klumpp and Fitzgerald, 2018 ), post-traumatic stress disorder ( Rauch et al, 2000 ), dementia ( Cavedo et al, 2011 ), and schizophrenia ( Prestia et al, 2011 ). Previous studies have shown that the amygdala is also involved in advanced cognitive abilities ( Belkhiria et al, 2020 ; Li et al, 2021 ), such as memory ( Adolphs et al, 1997 ; McIntyre et al, 2003 ; Schaefer et al, 2006 ; Taujanskaitė et al, 2020 ), learning ( Fried et al, 2001 ; Aquino et al, 2020 ), decision-making ( Bechara et al, 2003 ), reward behavior ( Sharp, 2019 ), and intelligence ( Gray et al, 2003 ; Li et al, 2021 ). In recent years, more and more studies have reported that the amygdala is associated with memory function, such as emotional memory ( Dolcos et al, 2017 ), memory consolidation ( Huff et al, 2013 ; Lalumiere, 2014 ), working memory ( Fried et al, 2001 ; McIntyre et al, 2003 ; Schaefer et al, 2006 ), state-dependent memory ( Baidoo et al, 2020 ), autobiographical memory ( Young et al, 2017 ), and episodic memory ( Kensinger et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Converging evidence indicates that cholinergic signalling from basal forebrain projections to local nicotinic receptors is an important physiological regulator of the basolateral amygdala and that nicotine alters this region's role in cognition, memory, motivated behaviours (e.g. promoting responding for natural reward), emotional states (anxiety and fear) and taking and seeking drugs (Sharp, ). Beyond the amygdala, the functional interactions between the cerebellum and medial prefrontal cortex were highlighted in forming drug‐cue associative memory, specifically the acquisition of cocaine‐cue Pavlovian associations (Gil‐Miravet et al ., ).…”
Section: Preclinical Modelsmentioning
confidence: 99%